Caracterização molecular do bag de capim-buffel da embrapa semiárido e avaliação da resposta á inoculação de bactérias diazotróficas - Araujo, Lucas Sampaio (2018)
Buffel grass (Cenchrus ciliaris) is of great importance for the semiarid region as a forage plant adapted to the region´s edaphoclimatic conditions region, such as high temperatures, water stress and high salinity of the soils. The main reproductive mechanism of this species occurs due to apomixis, since sexual reproduction is not available. Considering the importance of the species to the semi-arid region, Embrapa Semiárido created the Active Germplasm Bank (BAG), which has 115 accessions. Therefore, it is necessary to carry out studies that investigate the genetic and reproductive mechanisms of these accesses to determine the mechanism of sexual reproduction that presents itself in a process of genetic improvement of the culture. Genetic diversity evaluation allows for the selection of different accessions to perform diazotrophic interaction works, analyzing the capacity of symbiosis between plant / host. Biological nitrogen fixation in grasses can promote significant increases in productivity, nitrogen accumulation, and among other characteristics, reduce the use of chemical fertilizers to promote financial savings and reduce environmental impacts.The objective of this work was to perform the molecular and the response of five accessionsof buffel grass accesses through inoculation with diazotrophic bacteria. For the molecular characterization of the 115 accessions of the Embrapa Semiarido BAG, specific markers were used for the identification of the reproductive mode (SSR and SCAR) and genetic diversity (ISSR). After the molecular characterization, an experiment was carried out in pots without shade at Embrapa Semiárido.The experimente was a randomized block design with 4 replicates to evaluate the physiological characteristics using 5 genetically divergent accessions (CPATSA 134; CPATSA 432; CPATSA 558; CPATSA 572; Biloela) submitted to inoculation with 8 plant growth promoting bacteria. These accessions and bacteria were compared to absolute control treatments and pots treated with mineral N in the form of urea. The bacteria used in this experiment were Azospirillum brasilense, Herbaspirillum seropedicae, B10, B11, B12, B13, B16B16 previously isolatatedfrom buffel, S14 from sorghum.The bacteria strains from the Embrapa Semiárido collection. Two sexual accesses (CPATSA 102; CPATSA 134) were identified among the 115 in the BAG.These accesses can be incorporated into breeding programs of the species. The Biloela genotype and the CPATSA 134 access had significantly higherShoot Dry Mass (MSPA) and Total Nitrogen (NTOT) characteristics when inoculated with Azospirillum brasilense. The CPASA 134 access has the potential to be marketed, because it presented similar results to the Biloela (commercial) genotype.